Hubungan Sikap Kerja dengan Kejadian Low Back Pain (LBP) pada Pegawai Bank X di Kabupaten Gianyar - Ni Wayan Rusni; Ni Made Hegard Sukmawati; I Made Melvin Risma Putra (Aesculapius Medical Journal, 2022)
Low Back Pain (LBP) is a serious problem that has become the target of monitoring by the World Health Organization (WHO) as one of the top three problems. Low back pain is caused by several things such as trauma, tissue changes, and the influence of gravity. The purpose of this study was to determine the correlation between work posture and the incidence of low back pain (LBP) in Bank X employees in Gianyar Regency. The method of this study was an analytic observational with cross sectional approach. This study was conducted by total sampling on 35 respondents who involved inclusion and exclusion criteria. Low Back Pain was measured using the Rolland-Morris Disability Questionnaire (RMDQ), while Rapid Entire Body Assessment (REBA) was used to measure the working posture. The data were analyzed with Chi-Square Test using SPSS 26.0. The results were showed as followed: the low, mild, and high risk of working posture, 25.7 %, 34.3 % and 40.0 %, respectively; while the respondent with LBP was 57.1 %; The conclusion could be drawn that there was a correlation between working posture and LBP. It was recommended that the workers of the bank especially in the marketing department should be working postures in ergonomics approach.